Vocabulary test Strategies used by the Students to answer Vocabulary Test the Reading Comprehension of TOEFL - Suyatman Suyatman; Dzul Rachman (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2017)
Test of English as a foreign Language or TOEFL is a standardized test of English for non-native speaker. It consists of three parts or three sections of tests. In Reading Comprehension test, it consists of vocabulary test. To get better result of score, it needs strategies. The purposes of this study are to know the strategies used by the students to answer the vocabulary test on reading section of TOEFL, to know the most strategy used by the students, to know the least strategy used by the students and to know the distribution of strategies used by the students to answer the Vocabulary test of Reading Comprehension of the TOEFL. The researcher used descriptive qualitative research. The subject was twelve students. The instrument was questionnaire that consisted of thirty questions. Data analyzes technique was by using mean score. The result of the research showed that; (1) students used all strategies to answer the vocabulary test of reading comprehension of TOEFL. (2) the most strategies used by the students was ‘Looking for contextual clues to the meaning of unknown words.(3) the least strategy used by the students to answer vocabulary test was ‘Developing a new vocabulary study system, and (4) the distribution of the strategy number 1 was 3.88,strategy number 2 was 3.61, number 3 was 2.94, number four was 2.91, strategy number 5 was3.88, strategy number six was 3.47, strategy number seven was 3.69, strategy number eight was 3.02, strategy number nine was 3.00 and the last strategy was 3.13.